2017
DOI: 10.1080/02656736.2017.1375161
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy evaluation of catheter intraperitoneal chemotherapy, normothermic and hyperthermic chemoperfusion in a rat model of ascitic ovarian cancer

Abstract: Dioxadet and cisplatin show similar efficacy in the CIPC route. Compared with CIPC IP chemotherapy by chemoperfusions is more effective for both the drugs. Dioxadet in HIPEC showed highest survival benefit whereas largest effect during NIPEC is achieved with cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…It is demonstrated that holographic analysis of ovarian carcinoma cells taken from rats subjected to chemotherapy can be used for assessment of the treatment efficacy. The conclusions made were shown to be in agreement with recent results on the analysis of these cytostatics efficacy evaluated by experimentally determined survival rates of rats exposed to chemotherapy with these agents [33].…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…It is demonstrated that holographic analysis of ovarian carcinoma cells taken from rats subjected to chemotherapy can be used for assessment of the treatment efficacy. The conclusions made were shown to be in agreement with recent results on the analysis of these cytostatics efficacy evaluated by experimentally determined survival rates of rats exposed to chemotherapy with these agents [33].…”
Section: Introductionsupporting
confidence: 88%
“…The conclusions on the cytostatics efficiency made above were compared with the results obtained by the traditional biomedical test. The antitumor efficiency of both cytostatics was previously tested on the same rat model after a single intraperitoneal injection [32,33] and after hyperthermic intraperitoneal chemoperfusion (HIPEC) during surgery [41]. The drug efficiency was evaluated by the increase in median survival of animals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings may suggest additional toxicity of hyperthermia. In recent studies on rats with intra-abdominal inoculation of ovarian cancer, which were however not subjected to CRS, NIPEC with cisplatin was associated with less morbidity and a small, statistically non-significant, increase of survival when compared with HIPEC with cisplatin (59,60).…”
Section: Effect Of Different Treatments On the G 2 /M Subpopulationmentioning
confidence: 89%